Challenges On Teaching Online English Subject - Aisyah, Iketi (The Explora, 2020)
Online education continues to expand as distance learning grows in popularity. Today, most colleges and universities offer virtual classes in addition to their traditional in-person classes. This study aimed at identifying and describing the challenges faced by teachers in teaching online English subject in STAIN Mandailing Natal. English teacher as the subjects of this study is. This study applied a qualitative method. The research method used by researchers is by interviewing online. This study found that poor internet access experienced by students is a major problem. Students are often slow to respond to the process of learning activities carried out online. In addition, teachers also cannot directly measure students' ability. To reduce internet access problems experienced by students, the school facilitates internet data packages for teachers and students. In the end, this research is expected to be useful for English language teachers, readers, and schools to obtain information and be able to develop the quality of education.